2022
DOI: 10.3390/children9101553
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Coverage during Childhood and Adolescence among Undergraduate Health Science Students in Greece

Abstract: High rates of vaccination coverage in childhood represent one of the most important cost-effective tools of primary prevention and have substantially reduced the incidence of and mortality from vaccine-preventable diseases globally. Vaccination coverage of young people has not been well estimated in Greece. Anonymous self-completed questionnaires and the participants’ Child Health Booklet were used to estimate complete vaccination coverage of mandatory vaccinations against vaccine-preventable diseases of under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 44 publications
0
6
2
Order By: Relevance
“…We found no statistically significant difference in seroprevalence against measles between females and males and to our knowledge, sex differences regarding immunization coverage have not been suggested with the exception of one study which showed significantly higher vaccination coverage in females [18].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…We found no statistically significant difference in seroprevalence against measles between females and males and to our knowledge, sex differences regarding immunization coverage have not been suggested with the exception of one study which showed significantly higher vaccination coverage in females [18].…”
Section: Discussioncontrasting
confidence: 91%
“…However, a second dose is recommended for all children, which is essential to immunize the approximately 15% of them who do not develop protective immunity after their first dose [5]. A vaccination coverage >95% was also found via Child Vaccination Booklet in another published study conducted in the academic year 2020-2021 on health science undergraduate students, aged 18-30 years old [18]. However, studies based on vaccination certifications of specific social groups may overestimate the immunity levels and gives the false impression of an ideal seroepidemiological status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no statistically significant difference in seroprevalence against measles between females and males, and to our knowledge, sex differences regarding immunization coverage have not been suggested, with the exception of one study that showed significantly higher vaccination coverage in females [18]. Among seropositive individuals, as said before, a significant difference was observed between those younger than 40 years old and older individuals.…”
Section: Discussioncontrasting
confidence: 64%
“…However, a second dose is recommended for all children, which is essential to immunize the approximately 15% of them who do not develop protective immunity after their first dose [5]. Vaccination coverage of >95% was also found via the Child Vaccination Booklet in another published study conducted in the academic year 2020-2021 on health science undergraduate students aged 18-30 years old [18]. However, studies based on vaccination certifications of specific social groups may overestimate the immunity levels and provides the false impression of an ideal seroepidemiological status.…”
Section: Discussionmentioning
confidence: 99%